An Ultra Wideband Bandpass Filter based on Spoof Surface Plasmon Polaritons - SHU Yaohui; TANG Yiming; LI Zekun (Guangtongxin yanjiu)
【Objective】Spoof Surface Plasmon Polaritons (SSPPs) has the characteristics of low loss, high transmission efficiency, and strong binding ability to electromagnetic waves, which has been widely used in microwave device design. In this article, an ultra wideband Bandpass Filter (BPF) is proposed based on SSPPs, which features a simple structure, ease of processing, and excellent out-of-band suppression performance.【Methods】The BPF can be divided into two parts, a Coplanar Waveguide (CPW) high pass filter loaded with a pair of Split Ring Resonators (SRR) and a ring-shaped SSPPs low pass filter. The article is based on BPF design theory and SSPPs dispersion characteristics. It adopts modular and cascaded structural design methods to model the two parts of the structure separately. The dependency relationship between key structural parameters and performance indicators is studied. The tolerance analysis, sample development, and testing are also conducted.【Results】The proposed SSPPs low pass filter is composed of ring shaped SSPPs unit cells, which have better slow wave characteristics comparing with traditional I-shaped and T-shaped SSPPs unit cells. The proposed ultra wideband BPF has a passband range of 3.3~10.3 GHz. Its upper cut off frequency can be flexibly controlled in the structural design by changing the size of the SSPPs unit structure. The return loss within the passband of this BPF is better than -13 dB, with most insertion losses better than -1 dB. The out-of-band suppression reaches -25 dB for the lower stopband and -30 dB for the upper stopband. The rectangular coefficient within -20 dB is close to 1. The test results agrees well with the simulation results.【Conclusion】The developed BPF features a simple structure, convenient and low-cost processing, wide frequency band, and good steepness of the transition band. It can effectively realize signal filtering and out-of-band harmonic suppression functions, making it suitable for the development of circuits and equipment in related fields such as ridio frequency microwave communications and instrumentation measurements.